Tunable microstrip liquid crystals patch antennas. Issue 1 (November 2021) - Romanov, N A; Chimytov, T A; Nomoev, A V; Ch Khartaeva, E; Gurvitz, E A
Abstract: A patch antenna based on liquid crystals for the5G GHz range was simulated. The variation of the antenna frequency range after doping magnetic nanoparticles was verified. The high-frequency patch antenna parameters are calculated considering the dependence of the reflectivity of the antenna 11 on the dielectric anisotropy, gain, directivity and phase shift. The ability to control the frequency range of the patch antenna is shown. The phase distributions were demonstrated for 5CB crystals with a slight variation in the dielectric constant tensor and crystals with magnetic permeability.